Nebulized lidocaine alone or combined with fentanyl as a premedication to general anesthesia in spontaneously breathing pediatric patients undergoing rigid bronchoscopy. Issue 5 (28th November 2012) - Moustafa, Moustafa A.; Davidson, Andrew
Summary Introduction Pediatric bronchoscopy is an intensely stimulating procedure that requires a deep level of anesthesia to prevent hemodynamic overstimulation and straining. Topical anesthesia of the airway may be a beneficial component of the anesthetic technique to achieve adequate depth without residual sedation. Experimental evidence suggests that in addition to its central effects, locally applied opioids elicit potent analgesic effects. Methods Forty‐five patients aged 1–6 years scheduled for rigid bronchoscopy for foreign body removal were selected and subjected preoperatively to a nebulizer setting according to its components patients were divided into three groups. Group A: Nebulized solution contains 4 mg·kg−1 lidocaine 1%. Group B: Nebulized solution contains 4 mg·kg−1 lidocaine 1% plus 2 μg·kg−1 fentanyl. Group C: Nebulized solution contains 0.9% normal saline. Anesthesia was induced with 8% sevoflurane in 100% oxygen and maintained with continuous infusion of propofol 200 μg·kg−1. Increments of 500 μg·kg−1 propofol were given to the patient in case of straining or coughing. Patients were followed for the hemodynamics, the intraoperative difficulties, postoperative sedation score, time to full wakefulness and the postoperative complications. Results The hemodynamic parameters were much more stable in the fentanyl group relative to the other two groups. Also, the incidence of intraoperative difficulties was less significantly evident among patients in the fentanyl group (As regards cough P1 = 0.003, P2 = 0.0001, As regards the need to manual ventilation P1 = 0.037, P2 = 0.001, As regards Propofol increments P1 = 0.001, P2 = 0.001 where P1 refers to the fentanyl group relative to the lidocaine group, and P2 refers to fentanyl group relative to the placebo group). The postoperative sedation score was significantly higher, and the time to full wakefulness was significantly prolonged among patients in the fentanyl group relative to the other groups (P = 0.0001). Conclusion It is concluded that preoperative nebulized fentanyl reduces the hemodynamic response to bronchoscopy and decreases the intraoperative coughing in response to surgical manipulation without significant side effects except prolonged time to full wakefulness of patients.